2007
DOI: 10.1139/z07-005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of land use and climate on wetland breeding birds in the Prairie Pothole region of Canada

Abstract: Bird populations are influenced by a variety of factors at both small and large scales that range from the presence of suitable nesting habitat, predators, and food supplies to climate conditions and land-use patterns. We evaluated the influences of regional climate and land-use variables on wetland breeding birds in the Canada section of Bird Conservation Region 11 (CA-BCR11), the Prairie Potholes. We used bird abundance data from the North American Breeding Bird Survey, land-use data from the Prairie Farm Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
2
28
3
Order By: Relevance
“…, 1976), thereby increasing classification accuracy. Forcey et al. (2007) found little influence of land‐use variables on bird abundance in Canada, while many strong relationships occurred in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…, 1976), thereby increasing classification accuracy. Forcey et al. (2007) found little influence of land‐use variables on bird abundance in Canada, while many strong relationships occurred in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…The averaged data of all sites were used to determine the bird community every month Fig. 4 The number of wintering water birds significantly decreased in the newly formed lakeside from 2006 to 2011 foraging behavior, roosting locations, species composition and populations of water birds (Wan et al 2001;Armitage et al 2007;Forcey et al 2007). Studies confirmed that wetlands with more vegetation species and shallow water tend to attract more birds (Lindegarth and Chapman 2001;Hoover 2006;Riffell et al 2006;Cui et al 2009), and food is the most important factor that influence the distribution of water birds (Erwin 1983;Stillman et al 2010;Reid et al 2013).…”
Section: Wintering Water Birds and Dam Impoundmentmentioning
confidence: 99%
“…Weather data from both countries were used so that interpolations would span country borders and so that the maximum number of data points were available to interpolate (Forcey et al 2007). Total precipitation was calculated as follows:…”
Section: Historical Datasetsmentioning
confidence: 99%